PENGARUH EFEKTIFITAS SISTEM PENGENDALIAN INTERNAL TERHADAP KEBERHASILAN USAHA PADA SAME HOTEL KENDARI - Nining, Nining (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
Research entitled The Effect of the Effectiveness of the Internal Control System on Business Success at Same Hotel Kendari. This study aims to determine the effect of the effectiveness of the internal control system on business success at Same Hotel Kendari, data collection was carried out using a questionnaire. Data obtained from 30 people. Data analysis using simple regression. The analysis results show the regression equation Y = 7.022 + 0.605 X, this shows that if there is a change in the dimension of the Internal Control System by I unit, it will cause a change in performance by 60.5%. The effect of the Internal Control System on Business Success can be seen from the significance value of t in simple regression analysis, namely sig t = 0.00 < a = 0.05. The correlation coefficient (R) value of 0.809 means that the correlation between the independent variable Internal Control System (X) and Business Success (Y) is positive.